AVALIAÇÃO DE DESEMPENHO AMBIENTAL: O CASO DA BALSA GUINDASTE E DE LANÇAMENTO - BGL - Soibelman, Hélio José (2008)
The present work describes methodology directed to environmentalist s managers working with ferries that deals with underwater oil extraction in order to evaluate their (EMS) Environmental Management Systems performance. The study was developed throughout two methodological dimensions: Bibliographical and Field Research. The Bibliographical Research was described in chapter one. A Literature s review describing the evolution of environmental problems and ISO 14.001 and ISO 14.031 Norms were discussed, since they are employed by many organizations to administer their environmental demands. The work is qualified as a qualitative research since a field case study was carried out. A propel derrick and induction ferry (BGL) was investigated in order to answer the questions considered in the study s introduction. The aim was to integrate the evaluation process of environmental performance, like for instance: current policies, objectives and benchmarks analysis of Integrated Management System for the BGL. Moreover, the study intended to develop a methodology to identify benchmarks and to evaluate the impacts at BGL. It also intended to apply the methodology developed to identify benchmarks and significant impacts at the BGL. Afterward, to consider new environmental protection targets based on the significant aspects identified and to develop new environmental benchmarks based on the environmental targets proposed.